PEMBELAJARAN MENULIS TEKS RESENSI NOVEL DENGAN METODE DEMONSTRASI PADA SISWA SMA KELAS XI - Mohammad Aria Delvana; Diena San Fauziya (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This study discusses the learning of writing a novel reviewer. The research this time the author wants to try to apply the demonstration method to learning novel writing reviews which are expected to usually improve students' ability in writing novel reviews. The formulation of the problem in this research is whether there is a difference in the ability to write novel review texts at the pretest and posttest stages using the demonstration method? This study aims to determine the difference in review text writing at the pretest and posttest stages using the demonstration method. The method used in this study used pre-experimental design in the form of one-group interpretation-posttest design. Samples taken were 26 students. The instruments used in this study used the pretest and posttest question sheets. The results showed that the average student's pretest in writing a text received 40.2, while in the posttest stage it won 50.6. Thus the method of demonstration in the study of writing a novel reviewer text there are differences in the test results from pretest to posttest.